2021
DOI: 10.7759/cureus.20694
|View full text |Cite
|
Sign up to set email alerts
|

The Top 100 Most Cited Journal Articles in Pediatric Neurosurgery

Abstract: With the many papers published in the field of pediatric neurosurgery, it is often difficult to recognize those that have the most impact on future papers, i.e., citable papers. However, citation analysis allows one to better understand which papers are impacting the field the most. Therefore, the current study aimed to evaluate this literature. The Journal Citation Report database was searched for publications with the words “pediatric neurosurgery” or “pediatric neuro” in the title. Using the Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The focus of this study was to identify journal articles specifically dedicated to hydrocephalus. Using the same methods as Ponce and Lozano and later Grayson et al, 10 journals were identified using the Journal of Citation Report [ 6 , 7 ]. The database was searched using the terms “neurosurgery,” “neurological surgery,” “pediatric neurosurgery,” and “pediatric neurological surgery.” These journals were: Child’s Brain, Child’s Nervous System, Journal of Neurosurgery, Journal of Neurosurgery Pediatrics, Journal of Pediatrics, Neuropediatrics, Neurosurgery, Pediatric Neurosurgery, Pediatrics, and World Neurosurgery.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The focus of this study was to identify journal articles specifically dedicated to hydrocephalus. Using the same methods as Ponce and Lozano and later Grayson et al, 10 journals were identified using the Journal of Citation Report [ 6 , 7 ]. The database was searched using the terms “neurosurgery,” “neurological surgery,” “pediatric neurosurgery,” and “pediatric neurological surgery.” These journals were: Child’s Brain, Child’s Nervous System, Journal of Neurosurgery, Journal of Neurosurgery Pediatrics, Journal of Pediatrics, Neuropediatrics, Neurosurgery, Pediatric Neurosurgery, Pediatrics, and World Neurosurgery.…”
Section: Reviewmentioning
confidence: 99%
“…Given this, a centralized archive of pertinent literature is of great clinical value. Consistent with several new publications focusing on highly-cited literature within neurosurgery, we aimed to generate a list of the most relevant works on hydrocephalus published during the last four and a half decades [ 6 , 7 ]. Using bibliometric analysis, we created a catalog of the 100 most cited publications specific to hydrocephalus literature.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations